1977
DOI: 10.1116/1.569323
|View full text |Cite
|
Sign up to set email alerts
|

Surface and interface states on GaAs(110): Effects of atomic and electronic rearrangements

Abstract: Research during the last year has led to a better understanding of the electronic and atomic structure of the (110) surfaces of III–V semiconductors. In this paper we will briefly review these new developments as well as point out areas where agreement has been found between various experimental results presented in the literature. It is now generally agreed that there are no intrinsic surface states in the band gap on GaAs and the smaller band-gap materials (e.g., GaSb, InAs, and GaSb) and that Schottky barri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

1978
1978
1995
1995

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(18 citation statements)
references
References 0 publications
0
16
0
2
Order By: Relevance
“…Un exemple des caractéristiques 1 (V ) que nous avons obtenues sur des surfaces clivées vierges d'un échantillon de dopage 8 x 1017 cm-3 est donné figure 3. Il montre que les extra courants sont devenus très importants pour les deux métaux.…”
Section: Origine Des Extra Courants -L'origineunclassified
See 1 more Smart Citation
“…Un exemple des caractéristiques 1 (V ) que nous avons obtenues sur des surfaces clivées vierges d'un échantillon de dopage 8 x 1017 cm-3 est donné figure 3. Il montre que les extra courants sont devenus très importants pour les deux métaux.…”
Section: Origine Des Extra Courants -L'origineunclassified
“…Appl. 24 (1989) [45][46][47][48][49][50] décennies, a permis une avancée importante dans la compréhension de l'interaction métal-semiconducteur, en particulier dans le cas des composés III-V. Ces matériaux, outre leur intérêt technologique lié à la largeur de leur bande interdite ou à leur mobilité, peuvent présenter une surface exempte d'état électronique dans la bande interdite : c'est la surface (110) obtenue par clivage [3][4][5]. Il a ainsi été démontré que l'interaction de ces surfaces avec un métal (ainsi d'ailleurs qu'avec des atomes non métalliques) produit, dès les premiers stades du dépôt, un ancrage du niveau de Fermi qui explique en grande partie la valeur de la barrière 4>B mesurée dans les diodes Schottky [6][7][8][9].…”
unclassified
“…Such a high interface state density leads to surface Fermi level pinning which makes it impossible for making devices with optimal operation characteristics. 14 In contrast to GaAs ͑100͒, GaAs ͑110͒ can have a flat band up to the surface, 16,17 indicating the absence of both filled and empty surface states in the band gap. In short, it is found that a Si or Ge thin overlayer can form a heterojunction with GaAs and lower Schottky barrier heights 12,15 or unpin the GaAs surface Fermi level, while sulfur is effective in suppressing oxide formation and forming a stable S-Ga bond terminated surface.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical calculations show that intrinsic surface state density of GaAs is determined by the surface atom structure (Ivanov et al, 1980) and is highly dependent on the orientation. For example, the {110} surface is free of intrinsic mid-gap surface states (Spicer et al, 1977) whereas the mid-gap surface state density of both {100} surface and {111}B were reported to be high (e.g., for {100} it can reach 5 × 10 11 cm −2 ) (Offsey et al, 1986;Miller and Richmond, 1997) {112} can be considered to be comprised of {111} and {001} at a ratio of 2:1 (Joyce et al, 2010). For a free surface, this drastic difference is typically overwhelmed by the surface states introduced by oxygen (Spicer et al, 1977).…”
Section: Resultsmentioning
confidence: 99%
“…For example, the {110} surface is free of intrinsic mid-gap surface states (Spicer et al, 1977) whereas the mid-gap surface state density of both {100} surface and {111}B were reported to be high (e.g., for {100} it can reach 5 × 10 11 cm −2 ) (Offsey et al, 1986;Miller and Richmond, 1997) {112} can be considered to be comprised of {111} and {001} at a ratio of 2:1 (Joyce et al, 2010). For a free surface, this drastic difference is typically overwhelmed by the surface states introduced by oxygen (Spicer et al, 1977). Indeed, studies on bare GaAs nanowires showed near-identical surface recombination at uncapped {110} and {112} surfaces (Joyce et al, 2014).…”
Section: Resultsmentioning
confidence: 99%